2006
DOI: 10.1177/0363546505279915
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Transtibial Posterior Cruciate Ligament Reconstruction with Preservation of Posterior Cruciate Ligament Fibers

Abstract: In transtibial posterior cruciate ligament reconstructions, poor outcomes from the killer turn effect may be reduced by preserving the original posterior cruciate ligament fibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
91
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 36 publications
(48 reference statements)
2
91
1
1
Order By: Relevance
“…[19][20][21] This technique allows for easy viewing of the posterior structures and enables performance of correct positioning of the tibial tunnel of the posterior cruciate ligament and medial meniscus posterior horn during meniscal root repair in meniscal allograft transplantation. On the basis of this background, it was thought that the posterior side of the ACL femoral footprint could be observed from the PL side using a 70 arthroscope or trans-septal portal using a 30 arthroscope.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] This technique allows for easy viewing of the posterior structures and enables performance of correct positioning of the tibial tunnel of the posterior cruciate ligament and medial meniscus posterior horn during meniscal root repair in meniscal allograft transplantation. On the basis of this background, it was thought that the posterior side of the ACL femoral footprint could be observed from the PL side using a 70 arthroscope or trans-septal portal using a 30 arthroscope.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 However, techniques that preserve the remnant fibers have been introduced, under the assumption that such preservation contributes to postoperative posterior stability, grafted-tendon healing, and recovery of proprioception. [7][8][9] In addition, recent histologic studies have confirmed that portions of mechanoreceptors and vessels in PCL remnants can improve the biological healing status of grafted tendons. 10,11 Some authors, moreover, have reported that preservation of the original PCL fibers can reduce the killer-turn effect.…”
mentioning
confidence: 94%
“…The killer turn was associated with friction, graft stretch, and fatigue failure [4,[31][32][33]56]. Although some clinical studies have not found a difference between the transtibial and open inlay techniques [2,29], there is also a body of literature to suggest unsatisfactory results with residual laxity given the transtibial technique [10,21,25,53]. The tibial inlay PCL reconstruction technique was first introduced in 1995 to circumvent the killer turn of the conventional transtibial technique [3].…”
Section: Introductionmentioning
confidence: 99%